S128 A national real time online service dashboard could increase capacity for the delivery of acute non-invasive ventilation (NIV). (December 2018) - Smith, DP; Wyatt, J; Roberts, ME; Smart, J; Molyneux, AW
Abstract : Introduction: Inspiring Change, the 2017 NCEPOD report on Non-Invasive Ventilation (NIV) demonstrated major issues in treatment. 40% hospitals lacked capacity to deliver Acute NIV; the need to transfer patients and a lack of beds caused delays. 1 The BTS Quality Standards for Acute NIV state that hospitals must ensure that there is adequate capacity for Acute NIV. 2 We have previously demonstrated that an Acute NIV Prescription significantly reduced delays in treatment. However, we noted a lack of NIV capacity; data showed that 34% of our NIV referrals breached the 4 hour target. Methods: From Autumn 2017 we recorded the following 5 quality metrics for delivery of Acute NIV, at our daily 9 am board round on our Respiratory Support Unit: 1)Bed availability, 2)Nurse availability, 3)Consultant availability, 4)Ventilator availability, 5)Blood gas availability. We developed a realtime online dashboard to record these metrics, integrated with an escalation/bed policy for Acute NIV, with the aim to increase visibility of capacity, improve vigilance of service pressures, and flag issues with actions. Our policy was agreed with medical, nursing and bed managers. We introduced the dashboard/policy in Spring 2018, with no other additional investment. Data pre-and post-dashboard were analysed, see table 1. Results: Data for 76 days pre-dashboard showed that an NIV bed or nurse were only available on 39.5% and 35.5% of days, respectively. Data for 141 days post-dashboard showed significantly improved availability of an NIV bed, nurse and consultant, and an improvement in total score (out of 5, mean increasing from 3.6 to 4.6, p<0.00001) see table 1. Conclusions: We have demonstrated that a realtime online service dashboard, with an escalation/bed policy, significantly increased capacity to deliver Acute NIV. The dashboard utilised human factors and checklist methodology to increase situational awareness and influence decision-making to maintain a safe and efficient service. We believe such an approach is generalisable, and recommend the adoption of service dashboards/checklists as part of a National NIV Toolkit to help deliver better care. References: NCEPOD Inspiring Change. 2017. London. BTS quality standards for acute NIV in adults. BMJOpen RespRes 2018.